2019
DOI: 10.1111/imj.14346
|View full text |Cite
|
Sign up to set email alerts
|

Audit‐based measures of overuse of medical care in Australian hospital practice

Abstract: Overuse of care that does not confer benefit to patients and wastes limited resources is being increasingly recognised as a major healthcare problem. The preferred measure of overuse of a specific intervention is applying an evidence‐ or consensus‐based measure of inappropriateness directly to the medical records of individual patients who have received the intervention. This study aimed to assess the extent of overuse of care in hospital practice in Australia based on peer‐reviewed literature that reported cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Recently, troponin assays, as well as hospital admissions for chest pain in a low-risk patient population, have been reported as examples of overuse of care. 33 In our study, 21 of the rule-ins did not have an AMI. Ten of these patients were sent home with further management in primary care (table 2); none of them were readmitted with an AMI or died the following 90 days.…”
Section: Discussionmentioning
confidence: 46%
“…Recently, troponin assays, as well as hospital admissions for chest pain in a low-risk patient population, have been reported as examples of overuse of care. 33 In our study, 21 of the rule-ins did not have an AMI. Ten of these patients were sent home with further management in primary care (table 2); none of them were readmitted with an AMI or died the following 90 days.…”
Section: Discussionmentioning
confidence: 46%
“…Just under half (45%) of clinical encounters in Australia involving adults 10 are associated with failure to receive guideline‐recommended, disease‐specific treatments. In contrast, between 15% and 60% of investigations and treatments commonly used in hospital practice are unnecessary 11 …”
Section: Clinical Reasoningmentioning
confidence: 99%
“…As an example, a review investigating the overuse of testing in Australia found studies showing 34–62% of computed tomography scans of pulmonary arteries in suspected pulmonary thromboembolism, 36–40% of imaging tests in patients with low back pain, and 54% of imaging tests in patients with abdominal pain were unnecessary. 25 There are therefore likely opportunities for clinicians to reduce their use of low-value scans, or to substitute high-carbon modalities for low ones, such as using US in place of MRI when it is clinically appropriate to do so. For example, US is clinically preferred over MRI for shoulder impingement/rotator cuff symptoms, 26 and echocardiography has advantages over cardiac MRI when investigating asymptomatic patients in the context of inherited heart conditions.…”
Section: Discussionmentioning
confidence: 99%